Computational analysis of group 2 late embryogenesis proten (LEA) in different cultivar of bread wheat (Triticum aestivum) - Rasouli, Hassan; Kahrizi, Danial; Farshadfar, Ezatollah; Yari, Khirollach; Moradi, Mohammad Taher (Plant Breeding and Seed Science, 2014)
Late Embryogenesis abundant protein has a crucial role as the cold-acclimation process in the wheat. These proteins encoded by TaWdhn13 gene. This gene is transcriptionally activated and produces the accumu-lated proteins and metabolites and protection cell structure from freezing damage. The objectives of this study were to isolate the genomic DNA (g-DNA) sequence of TaWdhn13, to analyze structure, conserved domains of the gene, and to found a basis for association analysis of the functional sites associated with computational analysis. We here report on the functional assignment to TaWdhn13 gene by computational analysis. The Three-Dimensional (3D) model of LEA protein drawing by using the phyre 2 server. For identify the con-served domain and motif of these gene sequence we used the Conserved Domain Database and DNA Motif Searching Database, however, the conserved domains and motif has been recognized. The results showed TaWdhn13 conserved domain incudes: Dehydrin superfamily. Also, motifs structure for this gene includes: 2FE2S_FER_1 Motif, INTEGRIN_BETA Motif, VWFC_1 Motif, EGF_1 Motif and DEFENSIN Motif. Our results reveal that group 2 LEA proteins are most likely to function within the cell nucleus. The analysis of protein property showed that the protein had no trans-membrane domains. The isoelectric point of the protein was 3.41, which was charged with 5.34 negative electrons when pH value of the buffer was 7.0.